Prospects of Using Gum Arabic Silver Nanoparticles in Toothpaste to Prevent Dental Caries - Omnia Abdelmoneim Khidir Ahmed; Nicole Remaliah Samantha Sibuyi; Adewale Oluwaseun Fadaka; Ernest Maboza; Annette Olivier; Abram Madimabe Madiehe; Mervin Meyer; Greta Geerts (MDPI AG, 2023)
There is growing interest in the use of green synthesized silver nanoparticles (AgNPs) to control and prevent dental diseases. The incorporation of green synthesized AgNPs into dentifrices to reduce pathogenic oral microbes is motivated by their presumed biocompatibility and broad-spectrum antimicrobial activity. In the present study, gum arabic AgNPs (GA-AgNPs) were formulated into a toothpaste (TP) using a commercial TP at a non-active concentration, to produce GA-AgNPs_TP. The TP was selected after evaluating the antimicrobial activity of four commercial TPs 1-4 on selected oral microbes using agar disc diffusion and microdilution assays. The less active TP-1 was then used in the formulation of GA-AgNPs_TP-1; thereafter, the antimicrobial activity of GA-AgNPs_0.4g was compared to GA-AgNPs_TP-1. The cytotoxicity of GA-AgNPs_0.4g and GA-AgNPs_TP-1 was also assessed on the buccal mucosa fibroblast (BMF) cells using the MTT assay. The study demonstrated that antimicrobial activity of GA-AgNPs_0.4g was retained after being combined with a sub-lethal or inactive concentration of TP-1. The non-selective antimicrobial activity and cytotoxicity of both GA-AgNPs_0.4g and GA-AgNPs_TP-1 was demonstrated to be time and concentration dependent. These activities were instant, reducing microbial and BMF cell growth in less than one hour of exposure. However, the use of dentifrice commonly takes 2 min and rinsed off thereafter, which could prevent damage to the oral mucosa. Although, GA-AgNPs_TP-1 has a good prospect as a TP or oral healthcare product, more studies are required to further improve the biocompatibility of this formulation.